2013
DOI: 10.1002/bab.1130
|View full text |Cite
|
Sign up to set email alerts
|

Strain‐ and temperature‐dependent changes of fatty acid composition in Wickerhamomyces anomalus and Blastobotrys adeninivorans

Abstract: The fatty acid (FA) profiles of two strains of the yeasts Wickerhamomyces anomalus and Blastobotrys (Arxula) adeninivorans at cultivation temperatures from 15 to 30 °C were characterized. Besides the common even-numbered C16 and C18 FAs, substantial proportions of the uneven-numbered C17:1 were found in both species. C18:3(n-3) (alpha linolenic acid) made up to 3% of the total FAs in all strains. Considerable strain differences occurred, with regard to both the presence of single FAs and parameters like the do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…There was also a remarkable increase of heptadecenoic acid, C17:1 in R. babjevae during growth on hydrolysate. The occurrence of this fatty acid in yeasts has rarely been reported (Beltran et al 2008, Rossi et al 2009, Tronchoni et al 2012); however, we have recently found considerable amounts in the ascomycetes Blastobotrys adeninivorans and Wickerhamomyces anomalus (Olstorpe et al 2014). In the present study, we found detectable amounts of this fatty acid which were present in both L. starkeyi and R. babjevae .…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…There was also a remarkable increase of heptadecenoic acid, C17:1 in R. babjevae during growth on hydrolysate. The occurrence of this fatty acid in yeasts has rarely been reported (Beltran et al 2008, Rossi et al 2009, Tronchoni et al 2012); however, we have recently found considerable amounts in the ascomycetes Blastobotrys adeninivorans and Wickerhamomyces anomalus (Olstorpe et al 2014). In the present study, we found detectable amounts of this fatty acid which were present in both L. starkeyi and R. babjevae .…”
Section: Discussionmentioning
confidence: 65%
“…Granger et al (1992) only reported α- linolenic acid, (Munch et al 2015) did not differentiate between α- and γ-linolenic acid production in R. babjevae . α- and γ-linolenic acid have been observed in W. anomalus and B. adeninivorans (Olstorpe et al 2014), which are both not known as oleaginous yeasts. The mechanisms behind formation of α- and γ-linolenic acid need further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Olstorpe et al . () first described the temperature‐dependent fatty acid profile of C10 to C24 chain‐length fatty acids in A. adeninivorans (strains CBS 8244 and CBS 7377) . They found that C16:0 is the main fatty acid present in wild‐type strains (19.5–36.8% total fatty acids).…”
Section: An Apparently Ordinary Yeast With Some Extraordinary Propertiesmentioning
confidence: 99%
“…Swedish researchers already showed that the yeasts W. anomalus and Blastobotrys adeninivorans are very promising organisms for the production of microbial biomass, which would be used as a feed because they are able to grow on a variety of substrates and their chemical composition can be controlled by changes in growth conditions. In the paper by Olstorpe et al , this research group of Volkmar Passoth provides the results of first study of fatty acids composition of different strains of both species under different cultivation temperatures.…”
mentioning
confidence: 99%